Targeting climate-smart agriculture through farmer typologies in Kenya’s Central highlands - Kinyua, Michael; Muriithi, Cyrus; Notenbaert, An; Waswa, Boaz; Desta, Gizaw; Nyawade, Shadrack; Ofosu-ampong, Kingsley; Assefa, Banchayehu; Kihara, Job (2026)
The farmer segmentation analysis in Kenya’s Central Highlands Ecoregion Foodscape identified four distinct farmer typologies, highlighting substantial heterogeneity in resource access, climate exposure, soil health constraints, and production outcomes. Using household- and field-level data and multivariate clustering methods, the study demonstrates that farmers differ markedly in their capacity to adopt soil health, water-smart, and energy-smart practices. Results show that while resource-constrained, rain-fed farmers face high erosion and food insecurity, they are more inclined toward low-cost soil health practices, whereas irrigating and commercially oriented farmers achieve higher productivity but face emerging sustainability and nutrition challenges. Overall, the findings underscore the need for targeted, system-based climate-smart and regenerative interventions that align agronomic solutions with farmer context to improve productivity, resilience, and ecosystem outcomes.